A 3-year field study on lead immobilisation in paddy soil by a novel active silicate amendment. (1st January 2022) - Zhao, Hanghang; Zhang, Jianxin; Wu, Feng; Huang, Xunrong; Liu, Fuhao; Wang, Lu; Zhao, Xin; Hu, Xiongfei; Gao, Pengcheng; Tang, Bo; Ji, Puhui
Abstract: Lead (Pb) is a toxic metal in industrial production, which can seriously threat to human health and food safety. Thus, it is particularly crucial to reduce the content of Pb in the environment. In this study, raw fly ash (FA) was used to synthesise a new active silicate materials (IM) employing the low-temperature-assisted alkali (NaOH) roasting approach. The IM was further synthesised to form zeolite-A (ZA) using the hydrothermal method. The physicochemical characteristics of IM and ZA amendments before and after Pb 2+ adsorption were analysed using the Scanning electron microscope-Energy Dispersive Spectrometer (SEM-EDS), Fourier Transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) apparatuses. The results revealed the considerably change in the microstructure and functional groups of IM and ZA amendments, conducive to Pb 2+ removal. Moreover, a 3-year field experiment revealed that the IM and ZA significantly improved the growth of rice and reduced available Pb by 21%–26.8% and 9.7%–16.9%, respectively. After 3 years of remediation, the Pb concentration of the rice grain reached the national edible standard (≤0.2 mg kg −1 ) of 0.171 mg kg −1 and 0.179 mg kg −1, respectively. Meanwhile, the concentration of acid-exchangeable Pb reduced, while those of reducible and residual fractions of Pb increased. There was no significant difference between the IM and ZA treatments. The potential mechanisms of remediation by the amendments were ion-exchange, complexation, precipitation, and electrostatic attraction. Overall, the results indicate that IM is suitable for the remediation of contaminated soil and promotes safe food production, and develops an environmentally friendly and cost-effective amendment for the remediation of polluted soil. Abstract : Active silicon amendment has good remediation ability to lead contaminated soil, which can maintain the remediation effect for 3 years.